Open Digital Library, Implementation in Open Educational Perspective - Dhakal, Sushan (Kathmandu University Journal of Science, Engineering and Technology, 2007)
This paper focuses on the use of Open Digital Library in present educational scenario and the technical description of the architecture. The paper is based on the research and the development done in the Digital Library Research Lab using OAI-PMH and Php based harvester. The paper is presented with the flavor of Foss and Educational Theme.